2008
DOI: 10.1177/070674370805301211
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence and Characteristics of Clozapine-Induced Fever in a Local Psychiatric Unit in Hong Kong

Abstract: Objective: To determine the incidence, characteristics, and predictors of clozapine-induced fever in a sample of patients in a local psychiatric unit. Method: A retrospective review of case notes of 227 inpatients newly started on clozapine from March 2003 to December 2006 was conducted. Demographic characteristics, presence of fever, investigations carried out, fever characteristics, and complications of fever were recorded and analyzed. Patients with clozapine-induced fever were compared with their fever-fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…Furthermore, one group observed risk factors for fever occurring within the first 3 weeks of clozapine initiation that accord with those which Ronaldson et al. identified for myocarditis: concurrent sodium valproate and increasing rate of clozapine dose titration . Another group found the risk increased with age which is also so for myocarditis .…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…Furthermore, one group observed risk factors for fever occurring within the first 3 weeks of clozapine initiation that accord with those which Ronaldson et al. identified for myocarditis: concurrent sodium valproate and increasing rate of clozapine dose titration . Another group found the risk increased with age which is also so for myocarditis .…”
Section: Resultssupporting
confidence: 58%
“…Fever, developing prior to evidence of cardiac insult, is a common feature of myocarditis and has been reported in the literature from psychiatric services worldwide usually without reference to myocarditis (Table ). Retrospective chart reviews of patients commencing clozapine invariably report fever in a proportion varying from 1% to 44% . In addition to these chart reviews, eight case reports of fever in patients commencing clozapine have been published .…”
Section: Resultsmentioning
confidence: 99%
“…Prevailing theories include a mild variant of neuroleptic malignant syndrome, an allergic reaction, and the immunomodulating effects of the drug (16). The latter two theories are supported in the literature by several case reports and a prospective study, which have reported eosinophilia and elevated levels of cytokines, particularly interleukin-6 (IL-6) and tumor necrosis factor- α (TNF- α ), above what is already expected in schizophrenia, in the context of clozapine-induced fever (17, 2835). Additionally, clozapine has been demonstrated to have direct effects on these markers in adult patients with schizophrenia (28, 29, 32).…”
Section: Discussionmentioning
confidence: 77%
“…6,80 With respect to clozapine-associated fever, findings indicate that this is likely triggered by clozapine's proinflammatory effects on cytokine levels (e.g., IL-6) and is not likely attributed to neutropenia, a form of malignant neuroleptic syndrome, an allergic reaction, or direct effect on thermoregulation. 8,36 Clozapine-associated fever (as defined by temperature ≥ 38.0°C without an identified infectious source) occurs in 14%-26% of patients, 8,79,81 or as one study reported, occurs in 43.8% of patients when fever was defined with the lower threshold of 37.5°C. 82 There is some indication that clozapine-associated fever is more likely to develop in first time clozapine-treated patients, 8 older patients, 79 medically ill, those undergoing faster titration, and patients also receiving valproate.…”
Section: Monitoring Of Non-specific Signs and Symptoms Of Inflammationmentioning
confidence: 99%
“…81 Clozapine-associated fever tends to occur in the first 4 weeks of therapy. 8,80,81,83 Average duration of clozapine-associated fever was 1-5 days across different studies, though this may have been influenced by antipyretic administration. 8,79,81,83 Mean highest temperature was 38.8°C to 39.1°C.…”
Section: Monitoring Of Non-specific Signs and Symptoms Of Inflammationmentioning
confidence: 99%